2022
DOI: 10.1111/prd.12411
|View full text |Cite
|
Sign up to set email alerts
|

Reducing errors in guided implant surgery to optimize treatment outcomes

Abstract: Clinical considerations and treatment criteria in implant placement are constantly evolving. Prosthetically driven implant surgery has become the standard of care to improve short and long‐term functional and esthetic outcomes. Therefore, implant position and angulation are planned according to the available bone, anatomical structures, and the requirements of the future prosthetic superstructure. In parallel with these developments, significant progress has been made in data imaging and different software tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 61 publications
(163 reference statements)
0
52
0
Order By: Relevance
“…There are many ways that increased accuracy is expected to influence clinical outcomes. Some authors have suggested that CAIS could reduce intraoperative complications by helping the surgeon avoid damaging sensitive anatomic structures such as the mandibular nerve and the sinus, as well as avoid proximity to roots of neighboring teeth 4 . Some have suggested CAIS could reduce the invasiveness, complexity, and duration of surgical interventions, while others have reported increasing patients’ satisfaction and acceptance 5 .…”
Section: Introductionmentioning
confidence: 99%
“…There are many ways that increased accuracy is expected to influence clinical outcomes. Some authors have suggested that CAIS could reduce intraoperative complications by helping the surgeon avoid damaging sensitive anatomic structures such as the mandibular nerve and the sinus, as well as avoid proximity to roots of neighboring teeth 4 . Some have suggested CAIS could reduce the invasiveness, complexity, and duration of surgical interventions, while others have reported increasing patients’ satisfaction and acceptance 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Though the drill and surgical site’s motion are tracked in real-time, the CBCT images are undertaken with a registration device before the surgery. Therefore, the calibration must be performed before drilling with every change of drills to ensure accuracy in implant drilling and placement [ 25 ]. Compared to a static system, a dynamic navigation system has an inherently reasonable learning curve to allow for proficiency to be achieved [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were only 12 patients involved. Generally, two types of the CAIS technique have been introduced in the previous literature, described as static and dynamic guidance systems [25]. The static approach utilizes a pre-manufactured surgical template to guide drills and implants sequentially to the ideal planned position.…”
Section: Groupmentioning
confidence: 99%
“…Apart from numerous other potential advantages, the implementation of guided implant surgery also offers the benefit of ensuring an adequate cleansability, thus contributing to the maintenance of peri‐implant health. Chackartchi et al 16 contribute a state‐of‐the‐art review in this volume on “computer‐supported implant planning and guided surgery” that should encourage clinicians to revisit the potential advantages of this digital workflow.…”
Section: Iatrogenic Factors: Avoidable or Nonavoidable?mentioning
confidence: 99%